Les droits de l'enfant. Genèse, institutionnalisation et diffusion (1924-1989) - Moody, Zoe (Editions Alphil Presses universitaires suisses, 2016)
On November 20, 1989, the United Nations General Assembly ratified the Convention on the Rights of the Child. How is the evolution of the socio-legal status of the child that resulted in this Convention understood as well as the attitudes and strategies of stakeholders during the twentieth century? Through this book, Zoe Moody fills an important gap in the study of chil-dren's rights by analyzing for the first time the processes of genesis, institu-tionalization, and distribution of treaties on children's rights from a historical and transnational perspective.